An examination of the relationship between hypertension and healthy lifestyle behaviors in adults: Hypertension and healhty lifestyle - Can Arici, Ebru; Karadag, Gulendam (Progress in Nutrition, 2018)
Objectives: The modern lifestyle has led to an increase in the risk of hypertension and cardiovascular diseases. Design: This analytical cross-sectional study aimed to examine the relationship between hypertension and healthy lifestyle behaviors in adults. Participants: The research was carried out universe consisted of individuals aged 30+ years who applied to the family health center and the study sample included 400 individuals. Measurements: The participants’ weights, heights and blood pressures were measured, the data of the study were collected by using “Questionnaire Form” and “Healthy Lifestyle Behaviors Scale”. Results: 32.4% of the women and 31.0% of the men had blood pressures of 140/90 mmHg and above. Average BMI of the participants was 26.69+-4.39. The total point average of Healthy Lifestyle Behaviors Scale obtained by the of the participants was 121.86+-24.35. The participants on the subscales of self-realization, nutrition and interpersonal support were high, while the lowest score was obtained on the subscale of exercising. Further, those with lower blood pressure measurements were determined to have higher levels of self-realization, exercise, interpersonal support, stress management and healthy lifestyle behaviors compared to the levels of those with high blood pressure (p minor of 0.05). Conclusion: It has been determined that the male, who ate meals more frequently, with higher levels of physical activity, without chronic diseases, and the participants with normal blood pressure values had higher healthy lifestyle behaviors.